TECHNOLOGY AND THE GUILTY MIND: WHEN DO TECHNOLOGY PROVIDERS BECOME CRIMINAL ACCOMPLICES? - MARTIN, BENTON; NEWHALL, JEREMIAH (Journal of Criminal Law & Criminology)
The creators of today's most successful technologies share an important willingness to push the envelope--a drive that propels digital industry forward. This same drive, however, can lead some technology purveyors to push the limits of legality or even become scofflaws in their pursuit of innovation or (more often) profit. The United States must figure out how to harness the important creative force at the heart of the hacker ethic while still deterring destructive criminal wrongdoers. Because it is often courts that must answer this question, it is essential to examine the legal doctrines prosecutors use to sweep up technology providers. This Article focuses on one type of criminal liability--accomplice liability--that can act as a dragnet on providers of technology that lends itself to criminal use. In particular, a violation of the federal statute for aiding and abetting, 18 U.S.C. § 2, can be implied in every charge for a federal substantive offense, and there is a potentially troubling strain of cases holding that knowing assistance can be enough to deem someone an aider and abettor, even without stronger evidence of a shared criminal purpose. This Article examines when the proprietors of technology with criminal uses aid and abet their users' crimes. The aim is to help courts, prosecutors, and technologists draw the line between joining a criminal enterprise and merely providing technology with criminal uses. This Article explains the legal doctrines underlying this type of liability and provides examples of at-risk technologies, including spam software, file-sharing services, and anonymity networks like Tor. Ultimately, this Article concludes that the web of superficially conflicting rulings on the required mental state for aiding and abetting are best harmonized--and future rulings on liability for new technologies are best predicted--by looking to the existence of "substantial unoffending uses " for the product or service provided by the accused technologist.